Assessment of the Effect of Triton X-114 on the Physicochemical Properties of an Antibody Fragment - Pellegrini Malpiedi, Luciana (2014)
The effect of Triton X-114 on the physicochemical properties of a single-chain antibody fragment (scFv) has been studied. According to the far UV circular dichroism spectroscopy, the secondary structure of the recombinant antibody was not significantly affected by the presence of Triton. From the antibody tertiary structure analysis, it was found that the surfactant could be located around the tryptophan molecules accessible to the solvent, diminishing the polarity of its environment but maintaining most of the protein structure integrity. However, in certain conditions of high temperature and high concentration of denaturant molecules, the presence of TX could compromise the antibody fragment stability. These results represent a previous step in designing scFv purification protocols and should be considered prior to developing scFv liquid–liquid extraction procedures